2022
DOI: 10.4103/ijmy.ijmy_78_22
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Management of Hypersensitivity Reactions Developed Against Anti-Tuberculosis Drug

Abstract: Background: The World Health Organization Global Tuberculosis Report 2021 defines tuberculosis as the second infectious disease that causes sickness and death after COVID 19 and ranks it as the 13th among the global causes of death. However, the prevalence of the patients developing a hypersensitivity reaction against antituberculosis treatment is yet unknown. This study aimed to investigate the prevalence of drug allergy against antituberculosis treatment and the management of such a problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Immediate-type DHRs with antituberculosis drugs were reported to be developed in the early treatment period within days to a few weeks. 15 , 26 , 27 Compatible with previous reports, in this study initial DHR was developed within the first week in 132 (73.7%) cases; we also realized that it was on the first day of therapy in 86 (48.04%) cases. A previous study also reported that 14.7% of the antituberculosis DHRs were developed on the first day of therapy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Immediate-type DHRs with antituberculosis drugs were reported to be developed in the early treatment period within days to a few weeks. 15 , 26 , 27 Compatible with previous reports, in this study initial DHR was developed within the first week in 132 (73.7%) cases; we also realized that it was on the first day of therapy in 86 (48.04%) cases. A previous study also reported that 14.7% of the antituberculosis DHRs were developed on the first day of therapy.…”
Section: Discussionsupporting
confidence: 84%
“… 23 Some other studies reported that the female gender was a risk of antituberculosis DHR. 3 , 4 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…RIPE has been shown to be the most effective treatment for TB and alternative therapies are saved for use in the setting of multi-drug resistant TB and hypersensitivity to therapy. However, approximately 1–8 % of people who receive anti-TB therapy develop hypersensitivity reactions and alternative regimens must be evaluated [9] , [10] , [11] . We report a rare case of multiple-drug hypersensitivity to RIPE in an immunocompetent patient with a delayed diagnosis of CNS tuberculoma and our approach to treatment.…”
Section: Introductionmentioning
confidence: 99%